A rare case of plastid protein‐coding gene duplication in the chloroplast genome of Euglena archaeoplastidiata (Euglenophyta). Issue 3 (5th April 2017) - Bennett, Matthew S.; Shiu, Shin‐Han; Triemer, Richard E.
Abstract : Gene duplication is an important evolutionary process that allows duplicate functions to diverge, or, in some cases, allows for new functional gains. However, in contrast to the nuclear genome, gene duplications within the chloroplast are extremely rare. Here, we present the chloroplast genome of the photosynthetic protist Euglena archaeoplastidiata . Upon annotation, it was found that the chloroplast genome contained a novel tandem direct duplication that encoded a portion of RuBisCO large subunit ( rbc L) followed by a complete copy of ribosomal protein L32 ( rp l32), as well as the associated intergenic sequences. Analyses of the duplicated rpl 32 were inconclusive regarding selective pressures, although it was found that substitutions in the duplicated region, all non‐synonymous, likely had a neutral functional effect. The duplicated region did not exhibit patterns consistent with previously described mechanisms for tandem direct duplications, and demonstrated an unknown mechanism of duplication. In addition, a comparison of this chloroplast genome to other previously characterized chloroplast genomes from the same family revealed characteristics that indicated E. archaeoplastidiata was probably more closely related to taxa in the genera Monomorphina, Cryptoglena, and Euglenaria than it was to other Euglena taxa. Taken together, the chloroplast genome of E. archaeoplastidiata demonstrated multiple characteristics unique to the euglenoid world, and has justified the longstanding curiosity regarding this enigmatic taxon.